2022
DOI: 10.1186/s12866-022-02515-z
|View full text |Cite|
|
Sign up to set email alerts
|

Celastrol mitigates staphyloxanthin biosynthesis and biofilm formation in Staphylococcus aureus via targeting key regulators of virulence; in vitro and in vivo approach

Abstract: Background Staphylococcus aureus is a leading cause of human infections. The spread of antibiotic-resistant staphylococci has driven the search for novel strategies to supersede antibiotics use. Thus, targeting bacterial virulence rather than viability could be a possible alternative. Results The influence of celastrol on staphyloxanthin (STX) biosynthesis, biofilm formation, antibiotic susceptibility and host pathogenesis in S. aureus has been inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 84 publications
4
7
0
Order By: Relevance
“…Therefore, we selected several core genes for this study and found that they were significantly downregulated under the influence of geraniol. This is in agreement with phenotypic experiments ( Zhang et al, 2021 ; Yehia et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we selected several core genes for this study and found that they were significantly downregulated under the influence of geraniol. This is in agreement with phenotypic experiments ( Zhang et al, 2021 ; Yehia et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…The multi-omics analysis demonstrated that celastrol affected multiple metabolic pathways, including glycolysis, fatty acid metabolism, and the two-component system. Among them, carotenoid biosynthesis related to staphyloxanthin was inhibited after celastrol treatment, which was consistent with the results of a recent study by Yehia et al [45] Celastrol has been reported to exhibit anti-biofilm properties toward MRSA. [45] Results of the multi-omics analysis have led us to speculate this may be because celastrol can inhibit QS and TCS.…”
Section: Discussionsupporting
confidence: 90%
“…151 In S. aureus , celastrol inhibits a virulence factor called carotenoid staphyloxanthin (STX) which is essential for S. aureus to disrupt reactive oxygen species produced by host macrophages and neutrophils, thus reducing bacterial clearance by the innate immune system. 152…”
Section: Plant-derived Natural Products With Antimicrobial Activitymentioning
confidence: 99%